Designated survivor. The complete first season [videorecording (DVD)] - Sutherland, Kiefer, 1966-; McElhone, Natascha, 1969-; Canto, Adan, 1981- (Buena Vista Home Entertainment, 2017)
A low-level Cabinet member becomes President of the United States after a catastrophic attack kills everyone above him in the Presidential line of succession.